Microbiota disparities in stool, oral swabs, and saliva between control and early-onset colorectal neoplasia groups: an exploratory analysis - Na, Ji Eun; Kim, Tae Oh; Park, Yong Eun (Frontiers in Microbiomes, 2026)
Background/aimThe increasing incidence of early-age-onset colorectal neoplasia (EAO-CRN) in individuals under 50 years old poses a global health concern. This study aimed to investigate the variations in the microbiota in individuals with EAO-CRN compared with a control group, utilizing stool, oral swab, and saliva samples.MethodsParticipants under 50 years of age provided stool, oral swab, and saliva samples. Colorectal neoplasia was classified into the serrated lesions and adenoma–carcinoma groups based on histology and compared with a control group without polyps. The alpha diversity and the taxonomic abundance differences were assessed using amplicon sequence variants obtained through 16S rRNA sequencing and matched taxonomy data.ResultsA total of 45 participants were included: 14 in the control, 13 in the serrated lesions, and 18 in the adenoma–carcinoma groups. Microbial analysis revealed no significant differences in the alpha diversity among the groups. However, the stool samples from the serrated lesions group had higher levels of the families Erysipelotrichaceae and Lachnospiraceae compared with the control group. Analysis of the oral swabs indicated relatively elevated levels of the family Streptococcaceae in both the serrated lesions and adenoma–carcinoma groups. In the saliva samples, the serrated lesions and adenoma–carcinoma groups showed higher levels of the family Lactobacillaceae, with the serrated lesions group also exhibiting elevated levels of the family Bifidobacteriaceae.ConclusionsThis study elucidates the microbiota changes associated with EAO-CRN, distinguishing between serrated lesions and adenoma–carcinoma groups using stool, oral swab, and saliva samples. These findings contribute to the understanding of the relationship between microbiota and colorectal neoplasia in the early-onset population.